Increasing The Export Performance of Indonesian MSMEs' Leading Products in The Global Market in Supporting The Economy in 2023 - I Putu Artaya; Yuniningsih Yuniningsih; Che Zalina bt Zulkifli; Wasana Boonsong (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
This research activity aims to assist home-based businesses in an effort to improve their product marketability in the global market by improving several important things, including: improving raw materials, building distribution channels, managing sales networks, building their own brands for their products, improving the shape and quality of packaging. with good labeling so that the product can be accepted and able to compete abroad in a wider market. Through this study, researchers conducted interviews, and used research instruments to measure 73 business owners. The goal is that it hampers the process of increasing the export of its products to foreign markets, it turns out that with the results of the interviews it can be seen that there are 12 main variables or factors that must be mastered and/or improved. So that home-based business products can have better performance as desired by overseas buyers or consumers. The testing approach in data processing uses the Tau Kendall W Test combined with the Categorical Test, so that the estimation process can be carried out properly. Through the test approach model and interviews that have been conducted on 73 business actors, it can be seen that the 12 variables or factors stated in this research are the main keywords through improving input, process and product improvement outputs. Product changes can help change the buyer's perception that the products they buy are completely safe and comply with safety, health and material requirements, including parts of environmentally friendly materials.